Notification of crop varieties and registration of germplasm : Indian Dill, NRCSS AD-2 - Malhotra et al, S. K. (The Indian Journal of Genetics and Plant Breeding, 2017)
Indian dill (Anethum sowa Roxb.ex Flem) popularlycalled as sowa due to the presence of dillopiole ismostly grown for seeds (botanically fruits) as acommercial spice crop and find its use as an antispasmodic, anti-flatulent and carminative inpharmacological industry. The dill crop is mostly grownon marginal and sub-marginal lands, where input usedepends on the resource and management capacityon field scale with local varieties. Consequently, itsfull yield potential is not realized under arid to semiarid agro-climatic conditions. The productivity of dill(sowa) in India is quite low (480 kg/ha) as against thepotential of 1800 kg/ha. The National Research Centeron Seed Spices (NRCSS), Ajmer has succeeded indevelopment of first ever high yielding variety (NRCSSAD-2) of dill with high dillapiole content, for arid andsemi-arid agro-climate. ‘NRCSS AD 2 (Sel. AD-01-6)has been developed through mass selection basedon progeny performance from Nagaur Local. Theselection AD-01-6 was identified by the XVII All IndiaCo-ordinated Research Project on Spices as NRCSSAD 2 and released by State Varietal ReleaseCommittees of Rajasthan vide notification No. 3-43/2014-SD-IV dated 1.1.16. The 31st Subcommitteemeeting has approved the release of this variety forcultivation in the state and Ministry of Agriculture andFarmers Welfare, India accepted for notification of thisvariety in 24th Central Variety Release and NotificationCommittee meeting held on 22 September, 2016. Thisvariety has been registered at NBPGR with IC620541.